Paiements pour services environnementaux – de la theorie a la pratique en Indonesie - Romain Pirard; Raphaël Billé (VertigO)
A Payment for Environmental Services (PES) is a conservation tool that is commonly referred to by practitioners and researchers. Is is presented as an innovative approach that relies on voluntary transactions between suppliers and beneficiaries of a given environmental service, with associated (and previously agreed upon) conditions. Surveys of Indonesian sites have provided the authors with information enabling them to compare the implementation with the canonical and theoretical definition of PES, which applies a Coasean approach and a theory of property rights to the field of environmental services. On-the-ground implementation was also confronted to several important issues that would arise in the perspective of a large-scale application of the tool. Our study leads to the following lessons : (i) PES in practice contrast with the theory for reasons of feasibility ; (ii) economic evaluations of environmental services are under-utilized ; (iii) transaction costs appear to be a major obstacle ; (iv) the impact of PES on the role of public action is not obvious : on the one hand the polluter pays principle is put at risk and the State tends to be substituted by private actors, on the other hand a large-scale replication makes it necessary (and demanded by contracting parties) that public authorities take action ; (v) the activities defined as conditions for payments are productive and do not lead to freezing production in exchange for economic rents, for practical reasons mainly. Last, the gap between theory and practice might be partially due to a top down approach applied to a concept elaborated in the offices of economists, and this explanation is in line with previous analyses of the implementation of economic instruments for the environment.